People as a Service: a mobile-centric model for providing collective sociological profiles - García-Alonso, José; Miranda, Javier; Berrocal, Javier; Murillo, Juan Manuel; Canal-Velasco, José Carlos (My University, 2014)
Mobile devices have become increasingly popular in the everyday life of many individuals. By taking an insight into the most common uses of mobile devices we clearly appreciate that accessing internetbased services has grown greatly. This, and the fact that they are extremely personal gadgets has turned them into the main interface used by individuals to express themselves towards the outside world and to receive information from others. As a result of the highly personal use, mobile devices have been granted the potential to become unrivaled devices for building and storing the virtual profiles of their owners. Access to such profiles is of great interest in fields such as governance, health, smart cities, etc. Generating a centralized profile of a user is a task upon which a lot of interest has been put in the field of social mining. People-as-a-Service (PeaaS) is a computing model that seeks to establish the foundations upon which technologies that rely on mobile-centric computing models for social purposes should evolve.
Keywords: Sistemas de comunicación móviles